Repertórios de ação e classes sociais na onda de protestos de junho de 2013 - Tury, Joao Gabriel Loures [UNIFESP] (2017)
This dissertation has as object of study the repertoires of action and organization used in the wave of protests of June 2013. The research is based on the identification of the different phases that took place during the demonstrations: the first phase, the initial period of mobilization, was set up by the national confluence of waves of local protests related to public transport; the second phase, of diffusion and peak of mobilization, was characterized by a process of social and political overflowing, with the entrance of new sectors and new listo f claims in the protests; finally, in the third phase of demobilization, the reflux of demonstrations occurred. Next, we try to understand how the three main types of repertories among the demonstrators (the autonomist repertoire, the socialist repertoire and the patriotic repertoire) oscillated with the changes in the dynamics of the wave of protests. In this way, one can perceive how the autonomist repertoire, predominant in the first phase, starts to compete with the patriotic repertoire from the social and political overflowing. At this point of inflection, there is a breakdown of the unitary framing linked to the struggles for public transportation, and the (inorganic) relation between demonstrators and direction intentionally constructed by the Free Pass Movement - São Paulo changes, with an organizational vacuum. Identifying the specific repertories used by the demonstrators, the research seeks to highlight the importance of understanding the social classes and the class struggle to explain the constitution of forms of collective action. It is concluded that, in the wave of protests of June 2013, the combination of structural transformations with the interactions of the political process was responsible for the configuration of the predominant repertoires in the demonstrations.